Joint WDM and OAM Mode Group Multiplexed Transmission Over Conventional Multimode Fiber - Abhishek Mani Shukla; Sumanta Gupta (IEEE Photonics Journal, 2023)
To exploit the advantages of multimode fiber (MMF)-based transmission and to improve the overall capacity, transmission of OAM modes over a single wavelength needs to be replaced by multichannel transmission with the proper experimental demonstration in terms of achievable bit error rates (BER), cross-talk(x-talk), etc. over the entire transmission band. In this paper, we have experimentally shown the successful transmission of two OAM mode groups multiplexed signals jointly with three channels using wavelength division multiplexing (WDM) over a 1 km conventional MMF, namely OM3. In this experimental study, each OAM mode over each WDM channel uses 10 Gbps of on-off keying (OOK) modulation format. At the receiver end, the achieved bit error rate (BER) is found well below the required pre-FEC BER of $3.8× 10^{-3}$ without using any MIMO-DSP. To establish the efficacy of the signal transmission, the time evolutions of OAM mode x-talk and BER over wavelengths spanning the entire C-band have been experimentally measured. Under the influence of different x-talks, the BER performances of all three 50 GHz-spaced WDM channels for both OAM modes are measured. With proper adjustment of polarization at the receiver end, a BER value below the pre-FEC threshold is achieved over 900 seconds. The experimental results also revealed that the power penalty contribution of WDM x-talk is negligible compared to OAM mode x-talk.